Peran Korespondensi dalam Meningkatkan Efektivitas Komunikasi Organisasi - Salniati Nasution; Isnaini Sapritri Br. Purba; Rangga Hasibuan; Zahra Nabila Iqbal; Dara Avira; Tengku Darmansyah (Jurnal Manajemen Bisnis Era Digital, 2025)
Correspondence is one of the most important formal communication media in an organization because it functions to convey information clearly, systematically, and well-documented so as to support smooth communication between departments. This study aims to determine the role of correspondence in improving the effectiveness of organizational communication, as well as identifying challenges and solutions applied in its management. The method used is descriptive qualitative with data collection through interviews, observations, and documentation studies in an organization. The results of the study indicate that correspondence is effective as a formal communication tool that supports coordination between departments, although there are several obstacles such as late delivery and incorrect letter formats. Solutions such as administrative training, use of electronic filing systems, letter writing guidelines, and supervision have been proven to help improve the quality of correspondence. With good management, correspondence contributes significantly to improving the effectiveness of organizational communication as a whole.